2008
DOI: 10.1063/1.3020351
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic hindrance during the surface oxidation of Cu(100)–c(10×2)-Ag

Abstract: The influence of c(10x2)-Ag superstructure on the oxidation kinetics and oxygen adsorption-induced nanostructures on Cu(100) has been investigated as a function of O(2) exposure at 373 K by employing scanning tunneling microscopy and x-ray photoelectron spectroscopy. The oxygen adsorption-induced segregation of Cu through the Ag overlayer is found to trigger agglomeration of Ag and subsequent formation of ordered oval-shaped nanosize metallic Ag islands separated by Cu(100)-(2 radical2x radical2)R45 degrees -O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Therefore, oxygen coverage on Cu (100) surface and the resulted reconstructions have been the subject of numerous theoretical and experimental studies. [64][65][66][67][68][69][70][71][72][73] With STM technique, different reconstructed Cu (100) surfaces which depend on the oxygen coverage are observed. 72,73 At oxygen coverage less than 0.3 monolayers (ML), the surface is characterized by micro-domains formed in a c(2x2) arrangement, which can be describe as oxygen atoms occupying the 4-fold hollow sites.…”
Section: Oxidation Of Cu(100) Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, oxygen coverage on Cu (100) surface and the resulted reconstructions have been the subject of numerous theoretical and experimental studies. [64][65][66][67][68][69][70][71][72][73] With STM technique, different reconstructed Cu (100) surfaces which depend on the oxygen coverage are observed. 72,73 At oxygen coverage less than 0.3 monolayers (ML), the surface is characterized by micro-domains formed in a c(2x2) arrangement, which can be describe as oxygen atoms occupying the 4-fold hollow sites.…”
Section: Oxidation Of Cu(100) Surfacesmentioning
confidence: 99%
“…When the oxygen coverage rises above 0.5 ML, the missing-row reconstructed surface will be induced. 72,73 To study the interaction between oxygen molecules and the Cu surfaces with MD simulations, oxygen molecules are placed on Cu (100) surface, roughly 3Å ~ 5Å. The oxygen partial pressure is estimated around 100 oxygen atoms.…”
Section: Oxidation Of Cu(100) Surfacesmentioning
confidence: 99%
“…It has been reported that when there is CuO on a surface, there is almost certainly Cu 2 O as well. [45][46][47][48] Therefore, although the XPS data further conrms the formation of metallic Cu and Ag, it can only be inferred that some of the Cu particles were oxidized during the preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Similar reconstruction phenomena have been observed on Ag/Cu systems under oxygen exposure. 61 The electrochemical potential shift (DU, in V) for the onset of Pt dissolution relative to that on the Pt(111) surface signals the relative stability of the Pt surface atoms (in vacuum and under O) for the reaction Pt -Pt +2 + 2e À in acid medium. 42 It is found that all the 3d-metals (Co, Ni, Cu) having significant size difference with Pt are unstable in the core, and tend to segregate to the surface.…”
Section: Resultsmentioning
confidence: 99%